Numerical study on conjugate convective thermal transport in an annular porous geometry: DOI: 10.48129/kjs.10789 - S, Kiran; Mani, Sankar; Sivanandam, Sivasankaran (Kuwait Journal of Science, 2022)
Buoyancy-driven convection in an annular space between two upright concentric cylinders having finite thickness of inner/outer cylinder is an essential physical structure exposing several practical applications. The current article reports the coupled conduction-convection transfer in an upright porous annular space and the buoyant convective stream and thermal transfer, associated thermal transport rates has been numerically investigated. In this analysis, the inner cylinder has fixed width and maintained at uniform high temperature, while the outer cylinder wall is preserved at uniform lower temperature. However, the lower & upper boundaries of annular region are presumed to be sealed and insulated. The Brinkman-extended Darcy formulation is implemented for modeling the stream in the porous medium. An implicit finite difference technique based on SLOR & ADI methods is adopted to resolve the governing equations. From the numerical predictions, it has been detected that the conductivity ratio & wall thickness has crucial role in controlling thermal transport through the annular space. The present work will have applications in electronic equipment, electric machinery, solar collectors, and lubrication systems.